How Stress Facilitates Phenotypic Innovation Through Epigenetic Diversity - Srikant, Thanvi; Drost, Hajk-Georg (Frontiers in Plant Science, 2021)
Climate adaptation through phenotypic innovation will become the main challenge for plants during global warming. Plants exhibit a plethora of mechanisms to achieve environmental and developmental plasticity by inducing dynamic alterations of gene regulation and by maximizing natural variation through large population sizes. While successful over long evolutionary time scales, most of these mechanisms lack the short-term adaptive responsiveness that global warming will require. Here, we review our current understanding of the epigenetic regulation of plant genomes, with a focus on stress-response mechanisms and transgenerational inheritance. Field and laboratory-scale experiments on plants exposed to stress have revealed a multitude of temporally-controlled, mechanistic strategies integrating both genetic and epigenetic changes on the genome level. We analyse inter- and intra-specific population diversity to discuss how methylome differences and transposon activation can be harnessed for short-term adaptive efforts to shape co-evolving traits in response to qualitatively new climate conditions and environmental stress.